The Evolution of Contractual Liability in Smart Agreements: Legal Challenges of Blockchain-Based Transactions within Civil and Criminal Law Perspectives - H Muhamad Rezky Pahlawan MP; Baharuddin Riqiey (Journal of Civil Criminal Law, 2025)
Background: The rapid development of blockchain technology and smart contracts has fundamentally transformed contractual relationships by shifting the role of human interpretation and enforcement toward automated, code-based, and decentralized systems. This transformation generates complex legal implications, particularly regarding the evolution of contractual liability, which is increasingly distributed and no longer centered on a single legal subject. Objective: This study aims to analyze the evolution of contractual liability in smart agreements and examine how such transformation affects the fundamental principles of traditional contract law within modern legal systems. Methods: This research employs a normative and conceptual legal approach, supported by an analysis of blockchain regulations across multiple jurisdictions, case studies of smart contract implementation, and a comparative legal analysis between civil law and common law systems, complemented by a multidisciplinary literature review. Results: The findings indicate that contractual liability in smart agreements has evolved from a centralized fault-based liability model to an algorithmic, distributed, and code-dependent liability structure within blockchain ecosystems. This evolution creates new legal challenges concerning the attribution of liability, legal certainty, and the limitation of judicial intervention in automated contractual arrangements. Furthermore, the study identifies a tension between technological efficiency and substantive legal justice, highlighting the need for adaptive legal frameworks capable of accommodating decentralized technologies while ensuring the protection of legal rights and accountability of involved parties.